Meta-Analysis: Effectiveness of Enhanced Recovery After Caesarean Surgery (ERACS) on Length of Stay (LoS) - Pardomuan Robinson Sihombing (Epidemiology and Society Health Review (ESHR), 2026)
Background: Enhanced Recovery After Caesarean Surgery (ERACS) has evolved as a comprehensive perioperative care protocol to optimise patient recovery and reduce length of hospitalisation. Although individual studies show promising results, there has been no comprehensive meta-analysis of the effectiveness of ERACS on length of stay with a homogeneous methodology. This study aims to analyse the effectiveness of the ERACS protocol compared to conventional treatment on the length of hospitalisation through a systematic review and meta-analysis Method: A Systematic review was conducted following the PRISMA 2020 guidelines for studies that compared ERACS with conventional treatment in the section caesarea. Meta-analysis was performed using a random-effects model with the Jamovi software ESCI package. Heterogeneity was assessed using I² statistics, and sensitivity analysis was performed to test the robustness of the results. Results: Meta-analysis of 6 studies with a total of 820 subjects showed that the ERACS protocol significantly reduced the length of hospitalisation with a weighted mean difference of -21.6 hours (95% CI: -28.3 to -14.9, p = 0.001). Despite the high heterogeneity (I² = 99.5%), all studies showed consistent directional effects in favour of ERACS with a p-value of < 0.05 in all individual studies. Conclusion: Implementing the ERACS protocol provides significant clinical benefits in reducing the length of hospitalisation by almost 1 day compared to conventional treatment, with important implications for healthcare efficiency and cost-effectiveness.